METHODS OF LITERARY-PEDAGOGICAL ANALYSIS OF THE WORKS OF V. RASPUTIN (Symposium on Life and Environmental Sciences, 2026)
This article substantiates a methodological model for the literary-pedagogical analysis of Valentin Rasputin’s prose and publicistic heritage. The study proceeds from the assumption that Rasputin’s artistic world cannot be adequately interpreted only through plot description or thematic commentary, because his works organize a complex interaction of ethical conflict, memory, family responsibility, rural culture, ecological consciousness, speech culture, and the reader’s moral self-reflection. Therefore, the article proposes an integrated analytical framework that unites literary hermeneutics, axiological interpretation, characterological analysis, contextual-biographical reading, linguistic-stylistic observation, and pedagogical modeling. The research focuses on the educational potential of such works as “French Lessons,” “The Last Term,” “Live and Remember,” “Farewell to Matyora,” and “Money for Maria,” interpreting them as texts that form students’ capacity for empathy, ethical judgment, cultural memory, and reflective reading. The article also reviews Uzbek scholarly contributions connected with Rasputin studies and defines practical methodological directions for using Rasputin’s texts in literature education.
Keywords: Literary-pedagogical analysis, Valentin Rasputin, village prose, ethical education, cultural memory, hermeneutics, axiological method, reader response, literature teaching, moral reflection.